Synthesis, Characterization and Photocatalytic Activity of ZrO2 Nanoparticles using Mint Extract - Jasam, Noor Mohammed; Abdul Karem, Lekaa K.; Khalil, Ahmed M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This work describes a green synthesis route for zirconium oxide nanoparticles (ZrO2 NPs) by using Zr sulfate and mint extract. This method is distinguished from other processes (physical and chemical) by its simplicity, cost-effectiveness, and low potential risks during preparation. Multiple techniques have been used to characterize and analyze ZrO2 NPs, including Fourier transform infrared and ultraviolet visible spectra, crystal size calculation by X-ray diffraction, scanning electron and atomic force microscopes, energy-dispersive X-ray, and Zeta potential. Kinetic stability of the ZrO2 NPs system, as indicated by the Zeta potential of -25.8 mV, suggests a long-term persistence and high surface charge. Finally, photo-catalytic activities of zirconium oxide NPs were examined using methylene blue dye. The results showed that the dye's degradation efficiency under light irradiation was 96.88%, demonstrating its significant photo-catalytic potential. The x-ray diffraction analysis of the crystal size of ZrO2 NPs, using Debye Scherrer's equation, yielded a value of 18.78 nm. The prepared ZrO2 NPs were tetragonal